2010
DOI: 10.2337/dc09-2062
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss, Glycemic Control, and Changes in Cardiovascular Biomarkers in Patients With Type 2 Diabetes Receiving Incretin Therapies or Insulin in a Large Cohort Database

Abstract: OBJECTIVEWeight loss in patients with type 2 diabetes can improve glycemic control, lower blood pressure, and improve dyslipidemia. Glucagon-like peptide (GLP-1) receptor agonists are associated with weight loss and have potentially beneficial effects on cardiovascular risk biomarkers; however, there is limited information to indicate whether these effects remain outside of clinical trials.RESEARCH DESIGN AND METHODSMedical records from the General Electric Centricity research database were analyzed retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
127
3
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 22 publications
8
127
3
8
Order By: Relevance
“…It has been reported that the anti-diabetic peptides glucagon-like peptide 1 (GLP-1) and exendin 1-39 amide show beneficial effects in reducing cholesterol and triglycerides in diabetic subjects (Klonoff et al 2008, Rizzo et al 2009, Horton et al 2010. GLP-1, an incretin with insulinotropic and insulin-independent anti-diabetic properties (Creutzfeldt 2001), exerts insulin-3-like effects upon glucose metabolism in the liver, the skeletal muscle, and fat, apparently through a specific receptor different from that cloned in the pancreas (Valverde et al 1994, Delgado et al 1995, Villanueva-Peñacarrillo et al 1995, Yang et al 1998, Villanueva-Peñacarrillo et al 2001b, Sancho et al 2005, Arnés et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the anti-diabetic peptides glucagon-like peptide 1 (GLP-1) and exendin 1-39 amide show beneficial effects in reducing cholesterol and triglycerides in diabetic subjects (Klonoff et al 2008, Rizzo et al 2009, Horton et al 2010. GLP-1, an incretin with insulinotropic and insulin-independent anti-diabetic properties (Creutzfeldt 2001), exerts insulin-3-like effects upon glucose metabolism in the liver, the skeletal muscle, and fat, apparently through a specific receptor different from that cloned in the pancreas (Valverde et al 1994, Delgado et al 1995, Villanueva-Peñacarrillo et al 1995, Yang et al 1998, Villanueva-Peñacarrillo et al 2001b, Sancho et al 2005, Arnés et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the clinical trials, in line with animal studies, have reported a reduction of blood pressure after chronic treatment of GLP-1R agonists [148][149][150][151]. This may be explained, at least in part, by the ability of GLP-1 analogs to upregulate anti-oxidative enzymes and inhibit NFkB-mediated inflammatory signaling on endothelial cells [152,153], and to reduce oxidative stress by suppressing MAPK signaling pathways in peripheral lymphocytes of type 2 diabetic patients [154].…”
Section: How Conventional Diabetic Treatments May Ameliorate Endothelmentioning
confidence: 90%
“…5,[19][20][21][22] This report adds to the available literature exploring the use of large EMR databases to investigate questions related to the clinical care of patients with diabetes. 10,[23][24][25][26] There is no protocol-based implementation strategy for glycemic management in this population, meaning that this investigation reflects individual rather than protocol-driven practice. This provides data that extend beyond those limited to 1 particular insurance plan, where therapeutic interventions and data collection strategies may be more homogeneous.…”
Section: Discussionmentioning
confidence: 99%